2011
DOI: 10.1007/s12015-011-9256-4
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Mesenchymal Stem-Cells with Fibroblasts Accelerates Neurodegeneration in an Experimental Model of Parkinson’s Disease

Abstract: Pre-clinical studies have supported the use of mesenchymal stem cells (MSC) to treat highly prevalent neurodegenerative diseases such as Parkinson’s disease (PD) but preliminary trials have reported controversial results. In a rat model of PD induced by MPTP neurotoxin, we first observed a significant bilateral preservation of dopaminergic neurons in the substantia nigra and prevention of motor deficits typically observed in PD such as hypokinesia, catalepsy, and bradykinesia, following intracerebral administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 38 publications
4
23
0
Order By: Relevance
“…Liu et al [40] demonstrated that human bone marrow-derived MSC may accelerate human breast tumor growth in NOD/SCID mice by generating cytokines that affect the cancer stem cell population. Pereira et al [41] reported that co-transplantation of human umbilical cord-derived MSC with fibroblasts exacerbated neurodegeneration in a rat model of Parkinson's disease.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al [40] demonstrated that human bone marrow-derived MSC may accelerate human breast tumor growth in NOD/SCID mice by generating cytokines that affect the cancer stem cell population. Pereira et al [41] reported that co-transplantation of human umbilical cord-derived MSC with fibroblasts exacerbated neurodegeneration in a rat model of Parkinson's disease.…”
Section: Resultsmentioning
confidence: 99%
“…The author also pointed out that fibroblasts share a therapeutic potential with MSC [39]. Other authors and studies, however, have demonstrated that the contamination with fibroblasts can be one of the reasons why promising cell therapies are failing in the pre-clinical testing stages [8].…”
Section: Discussionmentioning
confidence: 99%
“…There were 20 experiments conducted to evaluate rotational behavior and 8 experiments conducted to evaluate limb function. In addition, there were three studies using the rotarod test [36,81,83] and three studies using the open field test [80,84,89]. Because of insufficient numbers, these studies on rotarod and open field were not included in the meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%